Suite of tools to help policymakers/stakeholders in West Africa to identify gaps in their national data systems to effectively track progress on nutrition and/or inform policy - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
To date, the resources including country-specific data notes, an accompanying technical note, a database, and a data visualization are all available online.